(untitled) (LEARNing Landscapes, 2014)
Using self-study of teaching and teacher education practices (S-STEP) research as an example, we explore intimate scholarship and the ways it captures particular lives and experiences within the educational world. To do that we define, explore, and consider how teachers and teacher educators can use this personal and vulnerable scholarship. We provide an example as evidence of ways that intimate scholarship in the form of S-STEP supports learning from experience. We assert that positioning researchers to examine what we know about teaching and being a teacher educator is profitable for the larger research conversation.